EVALUATION OF THE MAGHRIB MENGAJI PROGRAM IN LEBAK REGENT REGULATION NUMBER 4 OF 2013: CASE STUDY IN KP. MALANGNENGAH, BANJARSARI DISTRICT, LEBAK REGENCY - Saefudin Zuhri; Nurul Anriani (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
Reciting the Qur'an is an activity of reading the holy book of the Qur'an and is included in worship which has priority for Muslims. Recitation activities are more often carried out at night, which will be seen and heard in almost all Indonesian Muslim communities including Lebak Regency. The purpose of this study was to analyze the Implementation of Lebak Regency Regent Regulation Number 4 of 2013 concerning the Maghrib Koran Movement in Malang Nengah Village, Bendungan Village, Banjarsari District, Lebak Regency. The background of this research is the absence of the contact body and the Maghrib Koran Movement Council in Malang Nengah Village. In addition, there is no evaluation system from the Koran teacher for children who read the Qur'an in Malangnengah Village, so there is no clear indicator for children's ability to read the Qur'an. This research approach uses qualitative research. The results of the research were then analyzed using the Miles and Huberman Model. The results of this study indicate that the indicators of resources and bureaucracy are weak so that the implementation of Lebak Regency Regent Regulation No. 4 of 2013 concerning the Maghrib Movement in Malangnengah village is experiencing problems. However, the habit of reciting the Koran and children's ability to read the Qur'an were not directly affected by the Lebak Regency Regent's Regulation Number 4 of 2013 concerning the Maghrib Koran Movement.